Artificial Intelligence Technologies and Their Impact on Higher Education in Libya: A Field Study at the University of Benghazi - Abdalslam S. Imhmed Mohamed; Abdulrauf Montaser Ahmed Abdulrahman; Salah Mohmad Alsadq Aboghsesa; Amera H. M. Alzoubi (African Journal of Advanced Pure and Applied Sciences, 2025)
This study investigates the impact of Artificial Intelligence (AI) technologies on the quality of higher education in Libya, focusing on the University of Benghazi. While AI integration has globally transformed learning through adaptive platforms and automated assessments, Libyan institutions remain constrained by weak infrastructure, limited financial capacity, and insufficient faculty training. This qualitative case study, based on interviews with 18 participants (faculty lecturers, students, and administrators), explores the perceived benefits and obstacles associated with AI adoption. Findings reveal significant improvements in student engagement, assessment efficiency, and academic performance, with AI-supported courses achieving a 15% grade improvement. However, 90% of participants identified internet instability as a primary barrier, and 60% reported insufficient AI-related training. The study proposes policy recommendations, including targeted professional development programs, investment in digital infrastructure, and the formulation of ethical governance frameworks. This Study offers valuable insights for policymakers and educators in Libya’s evolving post-conflict educational landscape, contributing to the global discourse on AI’s role in higher education under resource-constrained contexts.